The Impact of Work Environment on Nurses' Compassion: A Multicenter Cross-Sectional Study - Sepideh Naseri MSc; Mansour Ghafourifard PhD; Akram Ghahramanian PhD (SAGE Publishing, 2022)
Introduction Compassionate care is considered as the main part of the nurses' identity and a core component of nursing care. One clinical environment where patients experience a lot of pain and nurses play a vital role in delivering care is the intensive care unit (ICU). Objective Considering the importance of compassionate care in intensive care units, this study aimed to assess the relationship between the work environment and nurses' compassion in intensive care units. Methods In this cross-sectional survey, a total of 235 nurses were randomly selected from the intensive care units of four educational hospitals of Tabriz University of Medical Sciences from January to March 2021. Data were collected by demographic questionnaire, the Sussex-Oxford Compassion for Others Scale (SOCS-O) and the Practice Environment Scale of the Nursing Work Index (PES-NWI). Results The results showed that there was a significant and inverse relationship between the patient per nurse ratio and the mean score of nurses' compassion ( P  < .05). Moreover, Pearson correlation coefficient showed that the mean total score of the nursing work index had a significant positive relationship with the mean score of the compassion for others (r = 0.16, P = .016). Conclusion Health care managers and leaders should pay more attention to the promotion of nurses' working environments and they should remove the organizational barriers of compassionate care delivery.